Penerapan Value Engineering untuk Efisiensi Biaya pada Proyek Bangunan Gedung (Studi Kasus: Proyek Pembangunan Gedung Variety Restaurant Batu Batam) - Indrastuti Indrastuti; Rina Mustifany (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
The cost efficiency of building construction projects is one of the challenges that are often faced in construction activities which of course will also faced in the construction of the Variety Restaurant in Batu Batam. Therefore, it is mandatory that every product or service meet the good standards and achieved through the fast fulfillment in terms of time and low costs. The study using Value Engineering a good solution because it aims a structured and creative problem solving effort to achieve cost efficiency in the construction of Batu Batam Variety Restaurant or in construction building in general. Value Engineering is carried out in several stages such as the information stage, the creative stage, the development stage and the presentation and proposal stages. By using the analysis of FAST Diagram and Pareto Diagrams, the two jobs that will be analyzed are sub-structure work and yard pavement work. The alternative solution chosen is to replace the bore pile foundation with the piling foundation and use asphalt as the main material for the pavement. The efficiency cost that could be obtained in the sub-structure work is Rp. 230,979,007.90,- or 19.4 % of the cost of the work reviewed while from the total overall project cost is 1.6 % and the savings in infrastructure work costs of Rp. Rp. 328,004,100,- or 12.8% of the cost of work reviewed and 2.14% of the total overall project cost. The total cost obtained from the savings in the Budget Plan after a VE analysis of Rp. 558,983,177.70,- or 3.7% of the total cost of the project.